Academic Aspiration for 10th- and 11th- grade Students from North Sharqiyah Governorate in the Sultanate of Oman - Al-Sayabiah, Asma’a; Al-Thafri ‎, Said; Emarah, Ehab (Jordan Journal of Educational Sciences, 2023)
This study aimed to study the role of academic self-efficacy beliefs as a mediating variable in the relationship between parenting styles and academic aspiration. The sample included 350 students randomly selected from 10th and 11th grade students in North Sharqiyah Governorate in the Sultanate of Oman. The measures of parenting styles (Al Dafri et al., 2011), academic self-efficacy beliefs (Pintrich et al., 1993), and academic aspiration (Abu-Hilal, 2000) were applied. The regression analysis by Baron and Kenny’s method showed a direct and positive association between motherly authoritative style, academic self-efficacy beliefs, and academic aspiration. The father’s authoritarian style and the mother’s permissive style directly and negatively affect academic aspiration. The results also showed a direct and positive effect of the authoritative style of the mother on the variables, as well as a direct and negative effect of the permissive style of the mother on the academic self-efficacy beliefs. The results also indicated that there is a direct and positive effect of academic self-efficacy beliefs on academic aspiration. Beside the direct effect, the results of Baron and Kenney’s method showed that academic self-efficacy beliefs play a mediation role in the relationship between parenting styles and academic aspiration through different and indirect effects, such as the indirect positive effect of the authoritative style of the mother on academic aspiration and academic self-efficacy beliefs and the indirect negative effects of the father’s authoritative style and the mother’s permissive style on academic aspiration and academic self-efficacy beliefs